Frictional properties of the wax coverings in Nepenthes alata slippery zone: results from AFM scanning - Wang, Lixin; Zhang, Shuoyan; Zhang, Shuoyan; Li, Shanshan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Slippery zone of Nepenthes alata presents anisotropic friction behaviors depending on its evolved structures. Studies have demonstrated the contribution of lunate cells, but the role of wax coverings has not been specially investigated. In this paper, we showed findings obtained from AFM scanning and SEM observation on characterizing the frictional properties of wax coverings. Friction data generated by the AFM cantilever on wax coverings along downward and upward directions were different. The difference was insignificant (2.56%) when applying the load force of 300 nN, but increased (4.83-8.40%) when applying the load force of 500-1500 nN. The scanned wax coverings showed no detectable damage when applying the load force of 300 nN, whereas observable damage was presented when the load force exceeded 500 nN. When the load force increased to 1500 nN, the wax coverings were destroyed completely. The results suggest the wax coverings depend on their surface morphology and structural characteristic to generate different frictional properties in different directions, but the difference was inconspicuous to declare the surface anisotropy. This study is helpful for further understanding the anisotropic properties of slippery zone, and motivates the slippery zone to be a bionic prototype for designing anisotropic surfaces.